Unilateral family therapy of alcohol dependence - Kalyoncu, Ö. Ayhan; Karagözoğlu, Mine (Journal of Dependence, 2003)
Family therapy has an important place in the treatment of alcohol dependence. Integration of family members into treatment has been found to facilitate the recovery process on the part of the patient. During this process, family members learn to deal effectively with negative feelings such as guilt, shame, and anger. In addition to this, they develop an understanding of effective ways of helping the patient taking into consideration the concept of co-dependence. In recent years, it has been observed that active involvement of family members in the treatment of alcohol dependence has a significant effect on bringing the patient into treatment as it has on facilitating the recovery process. Different family intervention methods had been developed in alcohol dependence. In this article, one of these which is named Unilateral Family Therapy, has been reviewed in terms of its theory and application.
Keywords: Alcohol dependence; family therapy; intervention